2016
DOI: 10.1002/met.1563
|View full text |Cite
|
Sign up to set email alerts
|

A flexible approach to defining weather patterns and their application in weather forecasting over Europe

Abstract: A method is presented for deriving weather patterns objectively over an area of interest, in this case the UK and surrounding European area. A set of 30 and eight patterns are derived through k-means clustering of daily mean sea level pressure (MSLP) data . These patterns have been designed for the purpose of post-processing forecast output from ensemble prediction systems and understanding how forecast models perform under different circulation types. The 30 weather patterns are designed for use in the medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
271
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 121 publications
(284 citation statements)
references
References 24 publications
7
271
1
1
Order By: Relevance
“…If poor distances coincide with a negative MSLP trend, then the assumption can be made that ensemble members have deeper areas of low pressure than their assigned weather patterns, which is potentially a sign of severe weather. Neal et al (, table 2) provide more examples for the interpretation of distance and correlation.…”
Section: Results Part 3: the Coastal Decider Forecasting Toolmentioning
confidence: 99%
See 3 more Smart Citations
“…If poor distances coincide with a negative MSLP trend, then the assumption can be made that ensemble members have deeper areas of low pressure than their assigned weather patterns, which is potentially a sign of severe weather. Neal et al (, table 2) provide more examples for the interpretation of distance and correlation.…”
Section: Results Part 3: the Coastal Decider Forecasting Toolmentioning
confidence: 99%
“…The underlying probabilistic weather pattern forecasts behind Coastal Decider are objectively verified for all models, with early results presented in Neal et al () for medium‐range ECMWF forecasts. Forecasts verified on a day‐by‐day basis and collated over all seasons were shown to have forecast skill out to at least 10 days for all weather patterns.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since synoptic weather conditions in the surrounding regions also affect the local weather (Neal et al . ), the MSLP fields used in this study cover the North Atlantic European region and central Europe (35 to 70°N, 30°W to 20°E; shown in Figure ); other studies have found this to be the optimal domain size for reconstructing surface temperatures from MSLP‐derived regime classifications (Beck et al . ).…”
Section: Calibration Using Analogues To the Current Forecastmentioning
confidence: 99%